Assembling affordances: towards a theory of relational affordances - Hopkins, Julian (AoIR Selected Papers of Internet Research, 2013)
Drawn from a long-term ethnographic research into personal blogging, this paper proposes a theoretical approach to the issue of materiality and culture in technology that combines the concept of affordances and that of Deleuze & Guattari’s concept of assemblage. Highlighting the relational aspect of these concepts, a list of blog affordances is proposed. These can provide a basis for further analysis of blogs as well as other internet media forms.